data design for integrating problem solving into frame-based programming - Nor Farahwahida Mohd Noor; Aslina Saad; Abu Bakar Ibrahim (Journal of ICT in Education, 2022)
Data design is one of the main types of design in software development. This paper aims to design a database for a programming application as a part of the application development process. The purpose of the application is to help students of Introductory Programming in the higher learning institutions of Malaysia solve programming problems in a programming environment, especially in the C language. The objective of the study is to produce a data design to integrate data from a problem-solving process into a frame-based programming environment. To achieve this objective, the study is adopting the user design part of the Rapid Application Development (RAD) Model. Six validated problem-solving steps which are based on computational thinking (CT) concepts combined with the input-process-output (IPO) Model were utilized to gather data in the problem-solving process. Then, these data were integrated into ten validated sets of programming Code Patterns to be utilized in the frame-based programming environment.  An entity-relationship diagram (ERD) which shows the relationship of seven entities was produced to illustrate the data design of the IPO database. This IPO database is the core of this programming application that integrates problem-solving into the frame-based programming environment. This integration contributes to the advancement of an integrated development environment (IDE) approach specifically for the needs of the novices. It helps to automate the instruction coding based on the guided problem solution, thus helping the novices to overcome the difficulties due to their incompetency in the programming language. Therefore, the design produced from this study is significant in developing an introductory IDE application for the students to improve their problem-solving and programming skills and prepare them for future demands of the industrial revolution challenges.